Embarrassment : poise and peril in everyday life - Miller, Rowland S. (New York : Guilford Press, 1996)
Embarrassment as a basic emotion
Embarrassing circumstances
A catalogue of embarrassments
The development of embarrassment
Personality and culture
The causes of embarrassment
Signs of embarrassment
Responses to embarrassment
Overcoming embarrassment
Bibliografija.
Kazalo
Keywords: poniženje; emocije; socijalna interakcija